Efeitos de um programa de exercícios em indivíduos com doença renal crônica submetidos à hemodiálise: um protocolo para ensaio clínico randomizado controlado - Silva, Lucas Ferreira Lopes da (2021)
Introduction: Chronic kidney disease is a kidney injury that progresses with progressive and irreversible loss of its multiple functions. The functional capacity (CF) of patients with chronic kidney disease (CKD) is decreased, with reduced physical activity and muscle weakness. Sleep disturbance is present in about 80% of these patients, implying recovery from other diseases. Efforts have been made to establish exercise programs for hemodialysis patients. Objective: To evaluate the effects of a rehabilitation program under CF and sleep quality (QS) in individuals with chronic renal failure undergoing hemodialysis. Experimental, quantitative study. Patients with a diagnosis of CKD undergoing hemodialysis (HD) at least three times a week will be included. The instruments used will be: Assessment Form, Borg Scale, Sleep Quality Assessment and Schedule (Pittsburgh and MCTQ), Quality of Life Questionnaire (WHOQOL-bref), 6-Minute Walk Test (6MWT), TUG Test (Timed Up and Go), Sit to Stand Test (STS). The intervention will last 12 weeks, being performed twice a week. The analysis will be performed using the Statistical Package For Social Sciences (SPSS) version 20 software. It is expected that the groups that will perform the physical therapy will obtain significant improvements regarding the CF and QS, compared to the control group.